Excursus in history: essays on some ideas of Irfan Habib - Parnaik, Prabhat (Tulika Books Delhi, 2011)
Excursus in History is an examination of Professor Irfan HabibHs work in different areas and an attempt to capture the totality of his thought. The essays in this volume are quite heterogeneous: some are in the nature of surveys of particular areas of Professor HabibHs work, some critically examine his positions, some elaborate upon his ideas and some carry his ideas forward. To familiarize the reader with Professor HabibHs overall intellectual project, there is an exhaustive interview with him in which he dwells upon a whole range of themes: from Mughal India to the freedom struggle to the problems of the Communist movement. And to give brief introductions to his seminal works, some book reviews that were published at the time his books came out are also included.Irfan Habib, Professor Emeritus of History at the Aligarh Muslim University, is the author of The Agrarian System (http://tulikabooks.wordpress.com/catalogue-2/recent-titles/history-2/excurses-in-history-essays-on-some-ideas-of-irfan-habib/)
Keywords: Habib, Irfan, 1931-; India - Historiography